Sierra Leone : Accounting and Auditing - World Bank (Washington, DC, 2012)
This report provides an assessment of accounting and auditing practices in Sierra Leone with reference to the International Financial Reporting Standards (IFRS) requirements issued by the International Accounting Standards Board, and International Standards on Auditing (ISA) issued by the International Federation of Accountants. This assessment is positioned within the broader context of the country's institutional framework and capacity needed to ensure the quality of corporate financial reporting. Efforts are necessary for strengthening the capacity of the regulators and ensuring compliance with applicable standards and codes. The accounting and auditing practices in Sierra Leone need to develop in line with a growing economy, as well as with international best practice. With the exception of banks and similar financial institutions, there is no legal mandate for other corporate entities to follow IFRS in preparation of financial statements and ISA in conducting audits. There are varying compliance gaps in both accounting and auditing practices. These gaps are likely to stem from lack of clearer understanding of professional accountants, inadequate technical capacities of the regulators, absence of implementation guidance, lack of independent oversight of the auditing profession, and shortcomings in professional education and training. Sierra Leone's accounting profession is dominated by members of the Association of Chartered Certified Accountants of the United Kingdom.